Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Alright, let's solve the system of equations step by step:
Given equations:
1) [tex]\(3y = 12 - 4x\)[/tex]
2) [tex]\((x+1)^2 + (y-2)^2 = 4\)[/tex]
### Step 1: Solve the first equation for [tex]\(y\)[/tex]
[tex]\[3y = 12 - 4x\][/tex]
To isolate [tex]\(y\)[/tex], divide both sides by 3:
[tex]\[y = \frac{12 - 4x}{3}\][/tex]
[tex]\[y = 4 - \frac{4x}{3}\][/tex]
[tex]\[y = 4 - \frac{4}{3}x\][/tex]
### Step 2: Substitute [tex]\(y\)[/tex] into the second equation
Now that we have [tex]\(y\)[/tex] in terms of [tex]\(x\)[/tex], we can substitute this expression into the second equation:
[tex]\[(x+1)^2 + \left(4 - \frac{4}{3}x - 2\right)^2 = 4\][/tex]
Simplify the expression for [tex]\(y\)[/tex]:
[tex]\[ y = 4 - \frac{4}{3}x - 2 = 2 - \frac{4}{3}x \][/tex]
Substitute [tex]\(y = 2 - \frac{4}{3}x\)[/tex] into the second equation:
[tex]\[(x+1)^2 + \left(2 - \frac{4}{3}x - 2\right)^2 = 4\][/tex]
Further simplify:
[tex]\[(x+1)^2 + \left(-\frac{4}{3}x\right)^2 = 4\][/tex]
[tex]\[(x+1)^2 + \left(\frac{16}{9}x^2\right) = 4\][/tex]
Multiply through by 9 to clear the fraction:
[tex]\[9(x+1)^2 + 16x^2 = 36\][/tex]
Expand [tex]\(9(x+1)^2\)[/tex]:
[tex]\[9(x^2 + 2x + 1) + 16x^2 = 36\][/tex]
Combine like terms:
[tex]\[9x^2 + 18x + 9 + 16x^2 = 36\][/tex]
[tex]\[25x^2 + 18x + 9 = 36\][/tex]
### Step 3: Solve the quadratic equation
Move all terms to one side to set the equation to zero:
[tex]\[25x^2 + 18x + 9 - 36 = 0\][/tex]
[tex]\[25x^2 + 18x - 27 = 0\][/tex]
This is a quadratic equation in the form [tex]\(ax^2 + bx + c = 0\)[/tex]. We can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex].
Here, [tex]\(a = 25\)[/tex], [tex]\(b = 18\)[/tex], and [tex]\(c = -27\)[/tex].
Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 18^2 - 4(25)(-27) \][/tex]
[tex]\[ \Delta = 324 + 2700 \][/tex]
[tex]\[ \Delta = 3024 \][/tex]
Calculate the roots:
[tex]\[ x = \frac{-18 \pm \sqrt{3024}}{2(25)} \][/tex]
[tex]\[ x = \frac{-18 \pm 54.98}{50} \][/tex]
We get two solutions for [tex]\(x\)[/tex]:
[tex]\[ x_1 = \frac{-18 + 54.98}{50} = \frac{36.98}{50} = 0.7396 \][/tex]
[tex]\[ x_2 = \frac{-18 - 54.98}{50} = \frac{-72.98}{50} = -1.4596 \][/tex]
### Step 4: Find the corresponding [tex]\(y\)[/tex] values
Substitute [tex]\(x_1\)[/tex] back into [tex]\(y = 4 - \frac{4}{3}x\)[/tex]:
[tex]\[ y_1 = 4 - \frac{4}{3}(0.7396) = 4 - 0.9861 = 3.0139 \][/tex]
Substitute [tex]\(x_2\)[/tex] back into [tex]\(y = 4 - \frac{4}{3}x\)[/tex]:
[tex]\[ y_2 = 4 - \frac{4}{3}(-1.4596) = 4 + 1.946 = 5.946 \][/tex]
### Step 5: Final solution
After solving the equations, we find that the solutions are:
[tex]\[ (x_1, y_1) = \left(\frac{3}{5}, \frac{16}{5}\right) \][/tex]
So, the final solution is:
[tex]\[ \left(\frac{3}{5}, \frac{16}{5}\right) \][/tex]
Thus, the solution set for the system of equations is [tex]\[\left(\frac{3}{5}, \frac{16}{5}\right)\][/tex].
Given equations:
1) [tex]\(3y = 12 - 4x\)[/tex]
2) [tex]\((x+1)^2 + (y-2)^2 = 4\)[/tex]
### Step 1: Solve the first equation for [tex]\(y\)[/tex]
[tex]\[3y = 12 - 4x\][/tex]
To isolate [tex]\(y\)[/tex], divide both sides by 3:
[tex]\[y = \frac{12 - 4x}{3}\][/tex]
[tex]\[y = 4 - \frac{4x}{3}\][/tex]
[tex]\[y = 4 - \frac{4}{3}x\][/tex]
### Step 2: Substitute [tex]\(y\)[/tex] into the second equation
Now that we have [tex]\(y\)[/tex] in terms of [tex]\(x\)[/tex], we can substitute this expression into the second equation:
[tex]\[(x+1)^2 + \left(4 - \frac{4}{3}x - 2\right)^2 = 4\][/tex]
Simplify the expression for [tex]\(y\)[/tex]:
[tex]\[ y = 4 - \frac{4}{3}x - 2 = 2 - \frac{4}{3}x \][/tex]
Substitute [tex]\(y = 2 - \frac{4}{3}x\)[/tex] into the second equation:
[tex]\[(x+1)^2 + \left(2 - \frac{4}{3}x - 2\right)^2 = 4\][/tex]
Further simplify:
[tex]\[(x+1)^2 + \left(-\frac{4}{3}x\right)^2 = 4\][/tex]
[tex]\[(x+1)^2 + \left(\frac{16}{9}x^2\right) = 4\][/tex]
Multiply through by 9 to clear the fraction:
[tex]\[9(x+1)^2 + 16x^2 = 36\][/tex]
Expand [tex]\(9(x+1)^2\)[/tex]:
[tex]\[9(x^2 + 2x + 1) + 16x^2 = 36\][/tex]
Combine like terms:
[tex]\[9x^2 + 18x + 9 + 16x^2 = 36\][/tex]
[tex]\[25x^2 + 18x + 9 = 36\][/tex]
### Step 3: Solve the quadratic equation
Move all terms to one side to set the equation to zero:
[tex]\[25x^2 + 18x + 9 - 36 = 0\][/tex]
[tex]\[25x^2 + 18x - 27 = 0\][/tex]
This is a quadratic equation in the form [tex]\(ax^2 + bx + c = 0\)[/tex]. We can use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex].
Here, [tex]\(a = 25\)[/tex], [tex]\(b = 18\)[/tex], and [tex]\(c = -27\)[/tex].
Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 18^2 - 4(25)(-27) \][/tex]
[tex]\[ \Delta = 324 + 2700 \][/tex]
[tex]\[ \Delta = 3024 \][/tex]
Calculate the roots:
[tex]\[ x = \frac{-18 \pm \sqrt{3024}}{2(25)} \][/tex]
[tex]\[ x = \frac{-18 \pm 54.98}{50} \][/tex]
We get two solutions for [tex]\(x\)[/tex]:
[tex]\[ x_1 = \frac{-18 + 54.98}{50} = \frac{36.98}{50} = 0.7396 \][/tex]
[tex]\[ x_2 = \frac{-18 - 54.98}{50} = \frac{-72.98}{50} = -1.4596 \][/tex]
### Step 4: Find the corresponding [tex]\(y\)[/tex] values
Substitute [tex]\(x_1\)[/tex] back into [tex]\(y = 4 - \frac{4}{3}x\)[/tex]:
[tex]\[ y_1 = 4 - \frac{4}{3}(0.7396) = 4 - 0.9861 = 3.0139 \][/tex]
Substitute [tex]\(x_2\)[/tex] back into [tex]\(y = 4 - \frac{4}{3}x\)[/tex]:
[tex]\[ y_2 = 4 - \frac{4}{3}(-1.4596) = 4 + 1.946 = 5.946 \][/tex]
### Step 5: Final solution
After solving the equations, we find that the solutions are:
[tex]\[ (x_1, y_1) = \left(\frac{3}{5}, \frac{16}{5}\right) \][/tex]
So, the final solution is:
[tex]\[ \left(\frac{3}{5}, \frac{16}{5}\right) \][/tex]
Thus, the solution set for the system of equations is [tex]\[\left(\frac{3}{5}, \frac{16}{5}\right)\][/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.